Māori Health: Issues relating to health care services - Elers, Phoebe (Te Kaharoa, 2014)
Since the colonisation of Aotearoa by the British, Māori have experienced health disparities in comparison to non-Māori.  While there have been numerous policies and initiatives to improve the diaspora, this is forecasted to continue for the Māori population.  The source of this health disparity is complex, being embedded in historic and contemporary inequities.  However, one prominent issue which continues to be reported, is the less than adequate health treatment received by Māori in comparison to those of non-Māori or non-Pacific origin.  According to the Ministry of Health, this is adversely contributing to Māori health inequalities. This paper discusses the difficulties confronted by Māori when accessing health care services.